Meningkatkan Prestasi Belajar Matematika Siswa SMP Al Hikmah Menggunakan Model Pembelajaran CORE - Muhammad Farid Nasrulloh; Mei Indrianah; Khusnul Khotimah; Wisnu Siwi Satiti (Jurnal Tadris Matematika, 2022)
The low achievement of student’s mathematics learning is a problem that must be considered and resolved. The teacher’s role in improving student achievement is very necessary. One of factors that influence student achievement is the selection of learning models. This study aims to determine an increase in student achievement after the implementation of the CORE (Connecting, Organizing, Reflecting, Extending) learning model. The type of research used is a quasi-experimental research with Pre-Experimental Design typye One Group Pretest-Posttest Design. Determination of the sample using saturated sampling technique. Subject of this research is all eighth graders in SMP AL Hikmah Balongrejo. Data collection techniques used are interviews, validation questionnaire, and learning outcomes test. While the research instrument uses learning outcomes test, namely pretest and posttest. Data analysis technique use validity test, reliability test, normality test, homogenity test, and paired sample t-test. Results showed significant level 0,000 > 0,05. It can be concluded that there is a difference in learning achievement (cognitive) between before and after the implementation of CORE learning model. Based on a review of the average student learning outcomes at the pretest and posttest, it was concluded that there was an increase in learning achievement after the implementation of the CORE learning model.